Modern Endoscopic Approaches to Video-Assisted Sentinel Lymph Node Biopsy and Axillary Lymph Node Dissection: A Review - R. M. Akhmedov; V. V. Konstantinova; A. B. Vats; A. S. Zhurov; Yu. V. Semiletova; A. A. Olchonova; A. M. Belousov; E. M. Bit-Sava; G. A. Dashyan (Инновационная медицина Кубани)
This article aims to analyze modern endoscopic techniques of sentinel lymph node biopsy and axillary lymph node dissection in breast cancer surgery.Owing to more accurate diagnosis and minimized patient morbidity and risks, endoscopic techniques have significantly expanded capabilities of breast cancer surgery.We review the main endoscopic techniques of sentinel lymph node biopsy and axillary lymph node dissection, analyze their efficacy and safety, and compare their benefits with those of conventional open techniques.The article discusses results of recent studies regarding diagnostic accuracy and complication rates. Furthermore, we discuss the impact of endoscopic axillary lymph node dissection on the prognosis and quality of life in patients with breast cancer.